Formulation Development and Characterization of Lumefantrine Solid Dispersion with Piperine for Solubility Enhancement (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Lumefantrine low/variable bioavailability with low aqueous solubility is associated with their crystallinity and P-glycoprotein (P-gp) mediated efflux. Herein, to improve the dissolution and hence the oral bioavailability, amorphous solid dispersions (SD) of lumefantrine (LUMF) containing piperine (PIP), a P-gp and CYP3A4 inhibitor, were prepared with Copovidone/Kollidon® VA 64 (KOL) at three different ratios with increasing content of the polymer. The PIP-LUMF-KOL SD at ratio of 1:6:18 demonstrated higher aqueous solubility of LUMF and hence were characterized by DSC, FTIR and XRD. The improved dissolution resulting due to loss of crystallinity of LUMF was confirmed by DSC thermogram and XRD diffractogram of LUMF-PIP-SD while FTIR studies investigated the possible intermolecular interactions between LUMF and PIP and /or KOL. DSC and dissolution experiments validated the stability of LUMFPIP-Sol SD for 90 days under stressed humidity and temperature conditions. Overall, the data suggest that the SD of LUMF incorporated with P-gp inhibitor PIP, enhances dissolution and hence could improve the bioavailability of LUMF.